MODIFIKASI MODULAR PRODUCTION SYSTEM (MPS) BERBASIS PROGRAMMABLE LOGIC CONTROL (PLC) SIEMENS - Al Abizari, Gaza; Syafitra, Fany; Febriansyah, Aan; Peprizal, Peprizal (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The automation process in today's industrial world has become a necessity to realize the industrial era 4.0. The automation process in production also improves many aspects ranging from time, quality, and quantity of production results. Therefore, automation personnel or technicians who are experts in designing, manufacturing, repairing, and maintaining the hardware and software used are needed. These skills must be prepared with training tools that support current industry standards. This research aims to improve and test the feasibility of devices. The methodology used in this research is planning tool repair, checking each component, repairing or replacing damaged components, and preparing a guidebook that will later be used in the learning process. Modular Production System (MPS) that will be modified is divided into three modules namely the distribution, processing, and sorting station. Each module has sensors, fiber optic, proximity, and there is an opto-electric sensor. The Programmable Logic Controller (PLC) device to be used is Siemens with Totally Integrated Automation (TIA) Portal Version 15. Testing is carried out to test the feasibility of the tool the quality of the module, and whether it is still feasible and can be used in learning. As well as increasing students' knowledge and competence.